What Is the Optimal Treatment for Liver Hydatid Cysts in Emergency and Elective Situations? - , Enver Zerem, Željko Puljiz, Boris Zdilar, Suad Kunosić, Admir Kurtcehajic, Omar Zerem (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Zerem E, Puljiz Ž, Zdilar B, Kunosić S, Kurtcehajic A, Zerem O. What is the optimal treatment for liver hydatid cysts in emergency and elective situations? Turk J Gastroenterol. 2024;35(2):158-159.